The European Union and Federalism: Thinking Outside the Box - della Cananea, Giacinto (Federalism as the Future of the Diverse EU?, 2025)
This chapter focuses on the European Union, viewed from the angle of the traditional distinction between states, both unitary and federal, and the unions of states. The chapter analyses critically what may be called the ‘ascending order’ approach to the study of modern polities; that is, an approach based on an increasing order or trend, without reversing direction, as well as on the assumption that the categories employed are intrinsically and necessarily different in some respects. An alternative approach, which is not based on rigid distinctions between the various types of modern polities, is then proposed. In the process of developing such alternative approach, the focus is on general principles. Keywords: European Union, ascending order, general principles, rule of law, supranational courts.